Effects of omega-3 supplementation on endothelial function, vascular structure, and metabolic parameters in adolescents with type 1 diabetes mellitus: A randomized clinical trial - Khorshidi, Masoud; Sayyari, Aliakbar; Aryaeian, Naheed; Olang, Beheshteh; Alaei, Mohammadreza; Khalili, Mitra; Hosseini, Amirhossein; Salehi, Masoud (Frontiers in Nutrition, 2022)
Background Vascular dysfunction is a major complication of diabetes that leads to cardiovascular disease (CVD). This study aimed to examine the effects of omega-3 consumption on endothelial function, vascular structure, and metabolic parameters in adolescents with type 1 diabetes mellitus (T1DM). Method In this randomized, double‐blind, placebo‐controlled clinical trial, 51 adolescents (10–18 years) with T1DM completed the study. Patients receive 600 mg/day (containing 180 mg EPA and 120 mg DHA) of omega-3 or placebo for 12 weeks. flow-mediated dilation (FMD), carotid intima-media thickness (CIMT), high-sensitivity C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR), triglycerides (TG), LDL, HDL, total cholesterol, BUN, creatinine, FBS, HbA1c, HOMA-IR, QUICKI, serum insulin (SI), urine albumin-creatinine ratio (uACR), blood pressure, and anthropometries were assessed at the baseline and after the intervention. Results Following supplementation, omega-3 significantly increased FMD (3.1±4.2 vs. -0.6±4 %, P=0.006) and decrease TG (-7.4±10.7 vs. -0.1±13.1 mg/dl, P=0.022) compared with the placebo group. However, no significant difference was observed regarding CIMT (-0.005±0.036 vs. 0.003±0.021 mm, P=0.33). hs-CRP significantly decreased within the omega-3 group (P=0.031); however, no significant change was observed compared with placebo group (P=0.221). no significant differences were observed regarding other variables. Conclusion Given the increment in FMD and reduction in TG, omega-3 supplementation can improve vascular function and reduce the risk of cardiovascular disease in adolescents with T1DM patients.